2024
DOI: 10.1101/2024.05.16.592602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of shell field populations in gastropods

Supanat Phuangphong,
Hiroki Yoshikawa,
Yune Kojima
et al.

Abstract: The embryonic shell field of mollusks first appears during gastrulation of the dorsal ectoderm and subsequently develops into the shell-secreting mantle in adult animals. Although several lines of evidence have revealed that this shell field lineage is exclusively derived from the second quartet (2q) of the 16-cell embryos, it is generally believed that the establishment of the shell field fate would be accomplished only after receiving inductive signals from the invaginated endoderm. Despite being accepted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…We showed that Gbx and Grainyhead specify the plate field and the remaining five genes specify the ridge. Our single cell transcriptome analysis of the gastropod Nipponacmea showed that Hox1 and engrailed mark the inner domain of the gastropod shell field, while Gata1/2/3, Pax2/5/8 and Goosecoid mark the outer domain of the shell field (Phuangphong et al, 2024). Johnson et al (2019) also shows that Hox1 and Pax2/5/8 - Goosecoid mark different zones of the shell field in the other species of gastropod Tritia .…”
Section: Resultsmentioning
confidence: 99%
“…We showed that Gbx and Grainyhead specify the plate field and the remaining five genes specify the ridge. Our single cell transcriptome analysis of the gastropod Nipponacmea showed that Hox1 and engrailed mark the inner domain of the gastropod shell field, while Gata1/2/3, Pax2/5/8 and Goosecoid mark the outer domain of the shell field (Phuangphong et al, 2024). Johnson et al (2019) also shows that Hox1 and Pax2/5/8 - Goosecoid mark different zones of the shell field in the other species of gastropod Tritia .…”
Section: Resultsmentioning
confidence: 99%